2021
DOI: 10.1038/s41598-021-96292-w
|View full text |Cite
|
Sign up to set email alerts
|

A novel CT scoring method predicts the prognosis of interstitial lung disease associated with anti-MDA5 positive dermatomyositis

Abstract: Anti-melanoma differentiation-associated gene 5-positive dermatomyositis-associated interstitial lung disease (MDA5+ DM-ILD) is a life-threatening disease. This study aimed to develop a novel pulmonary CT visual scoring method for assessing the prognosis of the disease, and an artificial intelligence (AI) algorithm-based analysis and an idiopathic pulmonary fibrosis (IPF)-based scoring were conducted as comparators. A retrospective cohort of hospitalized patients with MDA5+ DM-ILD was analyzed. Since most fata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…A new AI algorithm-based analysis suggested that “MDA5 score” may serve as an applicable prognostic predictor for MDA5 + DM-ILD ( 31 ). Regarding the laboratory examination indicators in our research, we found that poor prognosis patients had more positive and strongly positive anti-MDA5 results ( P = 0.024) than the survivors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A new AI algorithm-based analysis suggested that “MDA5 score” may serve as an applicable prognostic predictor for MDA5 + DM-ILD ( 31 ). Regarding the laboratory examination indicators in our research, we found that poor prognosis patients had more positive and strongly positive anti-MDA5 results ( P = 0.024) than the survivors.…”
Section: Resultsmentioning
confidence: 99%
“…However, the fibrosis components were heavily weighted in this scoring method. Recent research studies including an AI algorithm-based analysis named “AI score” revealed that lower zone GGO and consolidation demonstrated to be correlated with RP-ILD and were applicable prognostic predictors for MDA5 + DM-ILD ( 31 , 44 ). Besides, the scores of microhemorrhage, capillary disorganization, spontaneous pneumomediastinum, and neoangiogenesis were significantly correlated with known poor prognosis factors of DM-ILD and total fibrosis scores of chest HRCT ( 37 , 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, currently available HRCT scoring methods are observer dependent, with considerable inter-observer bias and initially derived for idiopathic pulmonary fibrosis (IPF) (8)(9)(10). When referring to MDA5 + DM-ILD with a much more aggressive clinical course, the applicability of the scoring system is controversial (11). Therefore, a measurable and quantitative method to assess severity and predict prognosis of MDA5 + DM-ILD is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study used deep learning and feature learning to obtain better segmentation results by training with large samples (23). Software package named "CT Pneumonia Analysis" applying in the similar mechanism was used in study by S Ye recently (24). Our design idea was to extent different.…”
Section: Discussionmentioning
confidence: 99%